2009
DOI: 10.1097/psy.0b013e31819e47d4
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Participation and Health: A Randomized Controlled Trial Among Medical Care Staff

Abstract: Fine arts stimulations improved perceived physical health, social functioning, and vitality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
1
10

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 16 publications
4
41
1
10
Order By: Relevance
“…This corresponds to some extent with the results reported by Bygren et al (2009), who did not found a significant impact of cultural attendance on similar measures of physical and mental health. As argued in section (5.3), however, comparing individuals that frequently visit cultural events (at least once a month) with others who rarely or never consume artistic goods and services may obscure the health benefits of cultural participation.…”
Section: Matching Estimates Of the Effect Of Cultural Participationsupporting
confidence: 91%
See 3 more Smart Citations
“…This corresponds to some extent with the results reported by Bygren et al (2009), who did not found a significant impact of cultural attendance on similar measures of physical and mental health. As argued in section (5.3), however, comparing individuals that frequently visit cultural events (at least once a month) with others who rarely or never consume artistic goods and services may obscure the health benefits of cultural participation.…”
Section: Matching Estimates Of the Effect Of Cultural Participationsupporting
confidence: 91%
“…Thus, we adopt a rather narrow definition of cultural participation that comprises both the performing arts and visual arts, which is however consistent with cultural economic approaches (Frey, 2008). To make our results comparable to previous experimental evidence (Bygren et al, 2009;Konlaan et al, 2000), the treatment indicator distinguishes between those who often go to cultural events and those who rarely or never attend cultural events. The treatment group is confined to individuals that visit cultural events at least once a month (n = 953).…”
Section: Definition Of the Treatment Variablesupporting
confidence: 63%
See 2 more Smart Citations
“…Cultural activities can enrich and enhance our memory and stimulate new neural pathways, they enable us to accelerate learning and to better comprehend our feelings, giving them meaning and context [20,21]. Cultural activities have also been shown to improve physical health, social function and vitality among health care staff [22]. Other initiatives, such as the Arts in Medicine (AIM) program, have been shown to reduce stress and increase revitalisation among nurses in their working environment [23].…”
Section: Introductionmentioning
confidence: 99%